Subunit Compensation and Plasticity of Synaptic GABAA Receptors Induced by Ethanol in α4 Subunit Knockout Mice - Suryanarayanan, Asha; Liang, Jing; Meyer, Edward M.; Lindemeyer, A. Kerstin; Chandra, Dev; Homanics, Gregg E.; Sieghart, Werner; Olsen, Richard W.; Spigelman, Igor (Frontiers in Neuroscience, 2011)
There is considerable evidence that ethanol (EtOH) potentiates γ-aminobutyric acid type A receptor (GABAAR) action, but only GABAARs containing δ subunits appear sensitive to low mM EtOH. The α4 and δ subunits co-assemble into GABAARs which are relatively highly expressed at extrasynaptic locations in the dentate gyrus where they mediate tonic inhibition. We previously demonstrated reversible- and time-dependent changes in GABAAR function and subunit composition in rats after single-dose EtOH intoxication. We concluded that early tolerance to EtOH occurs by over-activation and subsequent internalization of EtOH-sensitive extrasynaptic α4βδ-GABAARs. Based on this hypothesis, any highly EtOH-sensitive GABAARs should be subject to internalization following exposure to suitably high EtOH doses. To test this, we studied the GABAARs in mice with a global deletion of the α4 subunit (KO). The dentate granule cells (DGCs) of these mice exhibited greatly reduced tonic currents and greatly reduced potentiation by acutely applied EtOH, whereas synaptic currents showed heightened sensitivity to low EtOH concentrations. The hippocampus of naive KO mice showed reduced δ subunit protein levels, but increased α2, and γ2 levels compared to wild-type (WT) controls, suggesting at least partial compensation by these subunits in synaptic, highly EtOH-sensitive GABAARs of KO mice. In WT mice, cross-linking and Western blot analysis at 1 h after an EtOH challenge (3.5 g/kg, i.p.) revealed increased intracellular fraction of the α1, α4 and δ, but not α2, α5 or γ2 subunits. By contrast, we observed significant internalization of α1, α2, δ, and γ2 subunits after a similar EtOH challenge in KO mice. Synaptic currents from naïve KO mice were more sensitive to potentiation by zolpidem (0.3 μM, requiring α1/α2, inactive at α4/5 GABAARs) than those from naïve WT mice. At 1 h after EtOH, synaptic currents of WT mice were unchanged, whereas those of KO mice were significantly less sensitive to zolpi